2018
DOI: 10.1016/j.nmd.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Steroid therapy in an alpha-dystroglycanopathy due to GMPPB gene mutations: A case report

Abstract: Alpha-dystroglycanopathies are a group of progressive and untreatable neuromuscular disorders, due to aberrant alpha-dystroglycan glycosylation. We describe the effects of a short-term cycle of corticosteroid therapy in a 9-year-old boy, affected by an alpha-dystroglycanopathy due to GMPPB gene mutations. The patient was affected by a congenital progressive muscular dystrophy since the first month of life, associated with psychomotor delay, seizures, and congenital bilateral cataracts. Despite physical therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Nonetheless, it has also been observed that the same mutation may result in a disorder with or without impairment of neuromuscular transmission . The majority of reported patients with impaired neuromuscular transmission responded well to pyridostigmine, while isolated patients responded to 3,4‐DAP, salbutamol, or corticosteroids …”
Section: Hereditary Muscle Diseases With Neuromuscular Transmission Dmentioning
confidence: 99%
“…Nonetheless, it has also been observed that the same mutation may result in a disorder with or without impairment of neuromuscular transmission . The majority of reported patients with impaired neuromuscular transmission responded well to pyridostigmine, while isolated patients responded to 3,4‐DAP, salbutamol, or corticosteroids …”
Section: Hereditary Muscle Diseases With Neuromuscular Transmission Dmentioning
confidence: 99%